Quality of postoperative pain management among orthopedic patients in Hospital Universiti Sains Malaysia - Hasan, Norfazila Amir (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
The quality of postoperative pain management is both determine through assessment of postoperative pain and the outcome of satisfaction level. Postoperative pain is the pain experienced by orthopedic patients who underwent the operation. Good postoperative pain management indicates the high quality of postoperative pain management. This study aimed to determine the quality of postoperative pain management among orthopedic patients in Hospital USM, where can be determined through four subscales, communication, action, trust, and environment. A cross-sectional study had been conducted among 114 orthopedic patients obtained from three main orthopedic wards in Hospital USM. A self-administered questionnaire was provided in the ranged of age 18 to 74 who fit in inclusion criteria. The data were analyzed by using SPSS version 25.0 with the method of descriptive, independent t-test, and Pearson correlation coefficient test. The findings reported that the trust-related interventions were the highest score (M=18.88, SD=2.25) in determining the quality of postoperative pain management. Meanwhile, an independent t-test was used to statistically tested the differences between the site of pain and more pain than expected with the quality of postoperative pain management. Which showed there were no significant differences between the site of pain with the pain level at worst (p=0.404), least in the first 24-hours (p=0.700), pain experienced at day three of postoperatively, now (p=0.960), and level of satisfaction (p=0.071) of the quality of postoperative pain management. However, there was a significant difference between more pain than expected with the level of satisfaction of the quality of postoperative pain management (p=0.003). On the other hand, the Pearson correlation coefficient was used to analyze the relationship between communication, action, trust, and environment with the level of satisfaction to the quality of postoperative pain management. Surprisingly, the findings resulted in there were statistically significant, good and positive relationship between communication (r2=0.441, p<0.000), action (r2=0.389, p<0.000), trust (r2=0.303, p=0.01) and environment (r2=0.304, p=0.001) with level of satisfaction. In conclusion, the quality of postoperative pain management among orthopedic patients was good where mainly the effort to improved was influenced by trust-related assessment.